COSMETIC OUTCOME OF DERMOFAT GRAFT TO ANOPHTHALMIC ORBIT : JPUMHS;2024:14:02,39-45. http://doi.org/10.46536/jpumhs/2024/14.02.514 - Naz Ullah1, Samina Karim2, Asna Tahir3, Rafiq Mohammad4, Israr, Sohail5, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: As a severe and uncommon kind of eye absence, anophthalmia presents challenges for oculoplastic surgery due to potential consequences for both function and appearance. Dermofat graft (DFG)1 is a novel technique for anophthalmic orbit repair that offers advantages in terms of both appearance and functionality. However, literature demonstrating long-term cosmetic results is scarce to date and thus further studies are warranted. OBJECTIVE: To evaluate the cosmetic outcome of dermofat graft (DFG) to treat anophthalmic orbit, in order to achieve a natural orbital reconstruction with acceptable facial appearance. MATERIAL AND METHODS: This Prospective cohort study was carried out at Hayatabad Medical Complex Peshawar from June 2021 to December 2023. Twenty-seven adults 18-65 years of age with unilateral anophthalmia were enrolled. All of the dermofat graft surgeries were performed under general anesthesia. Data was collected through preoperative assessment, intraoperatively and monitor of post operative evaluation at monthly intervals up to 06 months. Descriptive statistics: Student T test was used for the analysis of continuous variables and frequency distributions were calculated in terms of percentages to compare groups using SPSS 23.0. RESULTS: Twenty-four (88.9%) of 27 patients were ultimately functional successes and cosmetically satisfied with their eye prosthesis following dermofat grafting. At 6 month follow up, cosmetic improvements were maintained in 92.5% of cases with minimal complications reported. Perhaps most remarkably, patient satisfaction with cosmetic results was a robust 91.7%. Of the 27 patients, three (11.1%) were managed by enucleation and 24 (88.9%), by evisceration. CONCLUSION: Dermofat grafts in anophthalmic orbit reconstruction lead to satisfactory functional results with marked improvement cosmetically and excellent patient satisfaction. Cosmetic outcomes were further enhanced by combining grafts with orbital implants.